PENGARUH SISTEM PENGENDALIAN INTERNAL PEMERINTAH (SPIP) DAN PERAN KOMITE SEKOLAH TERHADAP PENCEGAHAN FRAUD PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMP NEGERI DI BANDA ACEH - Ramadhani, Lisa; Suparno, Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to determine the effect of the Government Internal Control System (SPIP) and the role of school committee on the fraud prevention of management of school operational funds (BOS). The population of this research were headmaster, vice principal, and BOS treasurer of 19 Junior High Schools in Banda Aceh with the total 57 respondents. The research was conducted by using census method. The data source in this study are primary data obtained from questionnaires to the respondents. The testing of the influences of independent variables toward dependent variable was done by using multiple linear regressions model. The results of this research show that both partially simultaneously, Government Internal Control System (SPIP) and the role of school comittee are significantly influential to the fraud prevention of management of school operational funds (BOS) of Junior High Schools in Banda Aceh.